Four new species and new synonymy in Stenocerus Schoenherr, 1826 (Coleoptera, Anthribidae, Anthribinae, Stenocerini) - Lopes, Marcela Paes De A. M.; Mermudes, José Ricardo M. (Zootaxa, 2018)
Three new species from Brazil, Stenocerus christus sp. nov. (Rio de Janeiro, Corcovado), Stenocerus fratris sp. nov. (Espírito Santo, Santa Maria de Jetibá) and Stenocerus mesosternalius sp. nov. (Espírito Santo, Alegre, Fazenda Jerusalem), and a new species from Peru, Stenocerus similis sp. nov. (Mariscau, Juanjuí), are described and illustrated. Stenocerus paraguayensis Jordan, 1895 syn. nov. is proposed as a junior synonym of S. fulvitarsis (Germar, 1824). A key to all species of the genus Stenocerus is provided.